Diversification strategy and performance in Canadian manufacturing firms - Nguyen, The Hiep; Séror, Ann; Devinney, Timothy M. (Strategic Management Journal, 1990)
Abstract In a study of the interrelationships between firm diversification, market power, and performance, Montgomery (1985) presents empirical evidence in support of the hypotheses that highly diversified firms will have lower market shares in their respective markets than less diversified firms and that the strategy of diversification does not contribute to firm profitability. The present paper re‐examines these results with attention to the special characteristics of the open Canadian economy in a sample of Canadian manufacturing firms. The authors report evidence in support of the hypothesis that diversification in technologically related activities results in economies of scope and greater firm performance.